A study of Soil Invertebrates community in a Date - Palm plantation in Baghdad, Iraq - Baghdad Science Journal (مجلة بغداد للعلوم)
Soil invertebrates community an important role as part of essential food chain and responsible for the decomposition in the soil, helps soil aeration , nutrients recycling and increase agricultural production by providing the essential elements necessary for photosynthesis and energy flow in ecosystems.The aim of the present study was to investigate the soil invertebrates community in one of the date palms plantation in Aljaderia district South of Baghdad, , and their relationships with some physical and chemical properties of the soil , as Five randomly distributed replicates of soil samples were collected monthly. Invertebrates samples were sorted from the soil with two methods, direct method to isolate large invertebrates and indirectly to isolate small invertebrates using wet funnel method. The study also included the determination of physical and chemical factors of the soil (Temperature, Salinity, pH, Organic matter, Humidity, In addition to the soil texture).Monthly fluctuations in physical and chemical characteristics of the soil and the total invertebrates community study site were determined. Significant correlations the of the invertebrates community and each of temperature, organic matter, and humidity were observed. The study revealed that the temperature of the soil ranged between 5 to 25 C0 , The salinity concentration ranged between 1.1-1.9 ‰, The pH values ranged between 7.3 to 7.8 and the percentage of soil moisture ranged between 15 - 25% , Soil samples were composed of 44.6 % Clay, 19.7% Silt and 35.5% Sand.A total of 4625 individuals of soil invertebrates belonging to 16 taxa were sorted , within which the adult and larval insects were the most abundant, and from them 1283 individuals were sorted , represented 28% of the total numbers, followed by Isopoda , which 1030 individuals of them were sorted, In addition to Nematode, Oligochaetes Annelids family Enchytraeidae, and Earthworms family Lumbricida, Species of Chilopoda, Diplopoda, mites, land snails and slugs. The highest total individual number were recorded recorded durim moderate temperature months, February, March and April amounted to 838, 801 and 813 individuals, respectively.A significant correlation was mated between total number of soil invertebrates and each of temperature, organic matter and humidity. The significant difference in means was calculated according to LSD test.